Local conventions for natural resource management as tools for peacebuilding in central Mali: Case study in the agro-sylvo-pastoral systems of Sio, Fakala and Femaye Communes, Mopti Region - Ba, Baba (CGIAR System Organization, 2024)
Local conventions for natural resource management are essential tools initially implemented by the Kedo-Diren project, with the ambition of the Mali Resilient Challenge Fund Program project (MRCFP) to expand them on a larger scale in Central Mali, particularly in the Inner Niger Delta. These instruments aim to strengthen natural resource management while playing a role in peacebuilding in a region marked by insecurity and social and environmental challenges. A study was conducted to better understand the impacts of these conventions. The results highlight the multiple contributions of local conventions to peacebuilding. By facilitating the coordination of natural resources management, they have helped mitigate conflicts between farmers and herders through better communal spatial planning, particularly by rehabilitating and marking pastoral corridors. They have also enabled communities to develop collective rules and establish effective mechanisms for conflict prevention and management. The management conventions for bourgou resources have played a strategic role. They set rules for exploiting this essential resource and have promoted regeneration, supported bourgou cultivation and encouraged income-generating activities. These actions have strengthened the resilience of local communities while laying sustainable foundations for the peaceful and efficient management of shared resources.